Efficient DNA-Mediated Electron Transport in Ionic Liquids - Xuan, Shuguang (2017)
Electron conductivity of duplex DNA has promising applications in fabricating DNA based biosensors and electronic devices for biomimic solar cells. However, in aqueous solution DNA-mediated electron transfer (ET) is often far from ideal for these applications. We reported here that in hydrated ionic liquids (IL) electron can propagate through 4 nm of duplex DNA, and higher ET efficiency was achieved over longer distance which yielded a noncanonical negative distance decay parameter (γ = −0.02 Å–1). Fluorescence studies and ET efficiency of duplex DNA in IL-D2O revealed that the binding of both cationic and anionic species of hydrated IL in DNA minor groove and the exclusion of water from the DNA hydration layer significantly improved base-pair stacking of duplex DNA to achieve efficient electric conductivity. As an oxidation reaction of nucleic acids, efficient DNA ET observed here suggested that IL could be a promising nonorganic and nonaqueous solvent for redox reactions of biomacromolecules.